2017
DOI: 10.2196/mhealth.8741
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone Apps for Quality of Life and Well-Being Assessment in Breast and Prostate Cancer Patients: Systematic Review

Abstract: BackgroundMobile phone health apps are increasingly gaining attention in oncological care as potential tools for supporting cancer patients. Although the number of publications and health apps focusing on cancer is increasing, there are still few specifically designed for the most prevalent cancers diagnosed: breast and prostate cancers. There is a need to review the effect of these apps on breast and prostate cancer patients’ quality of life (QoL) and well-being.ObjectiveThe purposes of this study were to rev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 59 publications
(184 reference statements)
4
81
0
Order By: Relevance
“…Neither did we find evidence about participants' health outcomes being related to their use of TBIs (eg, completed all TBI sessions, discontinued use, or completed sessions over time). Our findings are consistent with the results from a previous systematic review of TBIs that showed that little studies monitored intervention dose (number of log on and website exploration) and its influence on HRQoL among breast and prostate cancer patients . Maintaining intervention use over time during study is a major moderator of TBI effectiveness and is likely to influence participants' long‐term health outcomes .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Neither did we find evidence about participants' health outcomes being related to their use of TBIs (eg, completed all TBI sessions, discontinued use, or completed sessions over time). Our findings are consistent with the results from a previous systematic review of TBIs that showed that little studies monitored intervention dose (number of log on and website exploration) and its influence on HRQoL among breast and prostate cancer patients . Maintaining intervention use over time during study is a major moderator of TBI effectiveness and is likely to influence participants' long‐term health outcomes .…”
Section: Discussionsupporting
confidence: 89%
“…Psychosocial and behavioral care delivered using technology‐based interventions (TBIs) has the potential to provide cost‐effective psychosocial care services to a large number of cancer patients and their families, to facilitate engagement in survivorship care, and to reduce the fear of stigma related to attending mental health services . Frequently used TBIs include web‐based programs, mobile apps, telehealth communication, and monitoring sensors to enhance individualized health care .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…for cardiovascular diseases [4], there are not any established solutions for palliative care patients. Various research on ICT systems has already shown some evidence on usage of web-based and mobile phone applications, e.g., to support symptoms management, to improve contact between patients and care givers over distance [5], [6] or intervention (e.g., nutrition, social network, physical exercises) apps to improve quality of life [7]. Andebe et al studied the usefulness of a mobile phone assessment in 15 palliative patients and caregivers in an African population by performing qualitative interviews after an usage period of 6 weeks [6].…”
Section: Prior Workmentioning
confidence: 99%
“…In recent years, attempts have been made to use mobile phone text messaging to achieve positive results for a range of health issues including treatment management and adherence (3)(4)(5), quality of life and well-being assessment (6), weight management (7,8), suicide prevention (9), smoking cessation (10), and other public health issues (11,12). Attempts have also been made to use mobile phone text messaging to address issues related to maternal and child health including interventions to support post-abortion contraception (13), infertility treatment (14), lactation management (15), and infant feeding (16).…”
Section: Introductionmentioning
confidence: 99%